Shinbone Pain and Fatigue are the Commonest Musculoskeletal Presentation in Vitamin D Deficiency - abdulhussein, mahdi abdulsahib (Karbala Journal of Medicine, 2020)
Abstract Background: In the past few decades, great attention has been paid to vitamin D deficiency and has been reported to be associated with a growing list of conditions. Nonspecific musculoskeletal manifestations are a common problem in vitamin D deficiency. The aim of this case series study was to explore the different nonspecific musculoskeletal presentations of this deficiency among adult people. Patients and methods: A descriptive study was designed to determine the prevalence of nonspecific musculoskeletal symptoms with vitamin D deficiency among adult patients visiting a private clinic in holy Kerbala/ Iraq during two years period. Result and discussion: Shinbone pain and fatigue were the most prevalent symptoms and showed positive association with vitamin D level. Other symptoms included low backache, proximal muscle ache and knee osteoarthritis. The association of these symptoms with demographic and anthropometric measures were explained. Vitamin D deficiency is a prevalent condition and need to be investigated even in countries with apparently high sun light exposure.